Representasi Ketidakadilan Perempuan dalam Novel Gadis Pantai karya Pramoedya Ananta Toer - Ni Made Ignityas Prima Astuti; Made Aditya Dharma; Aditya Ridho Fatmawan (Universitas Musamus Merauke, 2024)
This research aims to describe (1) the representation of women's injustice in the novel Girl Beach, (2) the representation of women's struggle in the novel Girl Beach by Pramoedya Ananta Toer. The design of this research is qualitative descriptive. The data source used is the novel Pantai Girl by Pramoedya Ananta Toer, published in 2003, 270 pages, publisher Lentera Dipantara, in Jakarta. The data collection technique that the author uses in this research uses the documentation method. The data collected was in the form of quotes regarding the representation of injustice and the struggles of female characters sourced from the novel Pantai Girl by Pramoedya Ananta Toer. The results of the research are that the main character in the novel Pantai Girl by Pramoedya Ananta Toer experiences injustice which includes subordination (assuming it is not important in decisions), stereotypes (negative labeling), violence (violence), and double burden (double burden), while the representation of the character's struggle in Fighting injustice in the novel Pantai Girl by Pramoedya Ananta Toer, namely the character Pantai Girl fights back by expressing opinions and resistance in the form of physical actions.